1998
DOI: 10.1007/s004410051188
|View full text |Cite
|
Sign up to set email alerts
|

A double-label analysis demonstrating the partial coexistence of tyrosine hydroxylase and GABA in retinal neurons of Ichthyophis kohtaoensis (Amphibia; Gymnophiona)

Abstract: Ichthyophis kohtaoensis is a limbless amphibian species with a subterranean mode of life and a predominantly olfactorily guided orientation. The only visually guided behavior seems to be negative phototaxis. As these animals possess extremely small eyes (only 540 µm in diameter in adults), functional investigations of the retina by electrophysiological single cell recordings have so far failed. Therefore, immunohistochemical transmitter studies constitute a starting point for a functional investigation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Starting from their first mention in the scientific literature as Serpens Caecilia Ceylonica (Seba ) and as reflected in their English vernacular derived from the Latin (caecus = blind) and the German name ‘Blindwuhlen’, caecilians have often been interpreted as having non‐functional, rudimentary visual systems associated with their mostly fossorial habits (Noble ; Walls ; Storch and Welsh ; Himstedt ). Although caecilian eyes are very small compared with those of most other amphibians, both absolutely and in relation to head and body size (Himstedt ), several more recent works have provided evidence from anatomy, behaviour, physiology, neurology and molecular biology that whereas caecilian eyes are reduced in many respects, they remain functional (Wake , ; Himstedt ; Dünker ,b, ; Mohun et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Starting from their first mention in the scientific literature as Serpens Caecilia Ceylonica (Seba ) and as reflected in their English vernacular derived from the Latin (caecus = blind) and the German name ‘Blindwuhlen’, caecilians have often been interpreted as having non‐functional, rudimentary visual systems associated with their mostly fossorial habits (Noble ; Walls ; Storch and Welsh ; Himstedt ). Although caecilian eyes are very small compared with those of most other amphibians, both absolutely and in relation to head and body size (Himstedt ), several more recent works have provided evidence from anatomy, behaviour, physiology, neurology and molecular biology that whereas caecilian eyes are reduced in many respects, they remain functional (Wake , ; Himstedt ; Dünker ,b, ; Mohun et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be pointed out that the catecholaminergic terminals described in different regions of the mammalian and avian brain (for review, see Papadopolous and Parnavelas, 1990;Karle et al, 1996;Metzger et al, 2002) show several cytological features in common with the DCgT2 terminals of the DLLv of the pigeon; both contain large dense-core vesicles and many small, round, synaptic vesicles throughout the axoplasm of their profiles. It has also been shown that in various structures of the central nervous system of a number of different species, the catecholaminergic neurons can also colocalize GABA (see Kosaka et al, 1987;Dunker, 1998;Diaz-Rios et al, 2002); catecholaminergic fibers have also been observed under the light microscope in the DLA of the pigeon (Gü ntü rkü n and Reiner et al, 1994). It is thus possible that at least one of the categories of DCgT terminals, while exhibiting GABA-immunoreactivity, are in fact the terminals of these fibers.…”
Section: Extrinsic Axonsmentioning
confidence: 94%